2023
DOI: 10.1371/journal.pone.0279809
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening polio vaccine demand in Ghana: Understanding the factors influencing uptake of the vaccine and the effectiveness of different message frames

Abstract: Background Ghana has experienced recent polio outbreaks. Behavioral insights can be used to understand behavior and create demand for the polio vaccine. Methods This cross-sectional study is based on an interactive mobile phone survey that explored factors influencing the uptake of the polio vaccine among Ghanaian mothers with children younger than five years old. The survey also explores the mothers’ intention to vaccinate their children in the future as well as an experiment with short polio vaccine voice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…At the same time, another study in Nigeria showed an enhancement in the overall number of childhood vaccinations due to SMS reminders [ 9 ]. Furthermore, other studies showed an increased number of vaccination visits due to mHealth in Benin [ 15 ], Kenya [ 11 , 16 ], Burkina Faso [ 17 ], Nigeria [ 18 ], Ghana [ 19 ], and Zimbabwe [ 20 ]. The above evidence shows reminders and vaccination information, which can be delivered through mobile phones, can potentially improve childhood vaccination [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, another study in Nigeria showed an enhancement in the overall number of childhood vaccinations due to SMS reminders [ 9 ]. Furthermore, other studies showed an increased number of vaccination visits due to mHealth in Benin [ 15 ], Kenya [ 11 , 16 ], Burkina Faso [ 17 ], Nigeria [ 18 ], Ghana [ 19 ], and Zimbabwe [ 20 ]. The above evidence shows reminders and vaccination information, which can be delivered through mobile phones, can potentially improve childhood vaccination [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mHealth-related challenges include poor usability, lack of system integration, poor data security and privacy, poor network access, and poor reliability [ 30 ]. In addition, other challenges such as low literacy, cultural constraints to accept mHealth, and healthcare-seeking behavior are prominent in Africa [ 15 , 19 , 31 , 32 ]. Additional challenges are related to poor standardization, a challenging regulatory framework, and poor overall health system readiness [ 33 ].…”
Section: Introductionmentioning
confidence: 99%